Rancang Bangun Sistem Pencarian Informasi Buku Berbasis Website Menggunakan Teknologi Semantik - Pramesti, Kadek Diah; Astuti, Luh Gede; Giri, Gst. Ayu Vida Mastrika; Kadyanan, I Gusti Agung Gede Arya (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Students of the Informatics Study Program at Udayana University often have difficulty finding appropriate reference books in the Informatics Study Program reading room. Through a semantic web and ontology approach, SISIBUK provides comprehensive digital information about books in the Informatics Study Program Reading Room. This system is equipped with browsing and search features. The research method used is Design Science Research Methodology (DSRM), with a Methodology method for modeling book ontology and a Prototyping method. Evaluation of system testing using the Blackbox Testing method and the Technology Acceptance Model (TAM) method. Blackbox Testing evaluation shows valid results in 12 test scenarios which indicate that the application is running according to function. Evaluation of the TAM method was carried out with a number of respondents, namely 50, showing results on the convenience variable of 90.51%, the usefulness variable is 89.73%, and the acceptance variable is 87.88%. which means very high acceptance of the SISIBUK application. With high hopes, this application can be a solution to the problem of searching for information on book collections in the Informatics Study Program Reading Room